The Detection of Pathogenic Fungi on Prayer Rugs of The Mosques at Jatinangor Campus of Universitas Padjadjaran - Faturrachman Faturrachman; Yanti Mulyana (Universitas Kristen Maranatha, 2019)
Fungus easily grows in the plateau area with warm moist air. The fungus can enter and contaminate mosque rooms, especially on the surface of prayer rugs. If pathogenic fungi grow on prayer rugs, they can increase the health risk of those who come into contact with them. This research aimed to detect and identify pathogenic fungi on prayer rugs of the mosques in Jatinangor campus of Universitas Padjadjaran using laboratoric descriptive method. The data was collected by sampling of dust from the surface of prayer rugs, fungal culturing and mold identification. The existence of pathogenic fungi has been investigated and observed in twenty-eight samples of thirty mosques using simple random sampling. Sabouraud Dextrose Agar was the chosen medium to grow pathogenic fungi. We found fungal growth in all samples with a total of 8 fungal species (Alternaria spp, Aspergillus spp, Candida spp, Fonsecaea spp, Mucor spp, Penicillium spp, Rhizopus spp, Rhodotorula spp) which are opportunistic fungi; however, no pathogenic fungi were found.Keywords : pathogenic fungi, prayer rugs, fungus, Aspergillus spp., Candida spp.